Unity, individuality and uniqueness of the person in the risk/benefit balance of the use of nutrigenetic tests in clinical practice - De la Garza, Ana Laura; Zonenszain-Laiter, Yael (Acta Bioethica, 2022)
In recent years, whole genome association studies have been conducted to identify genetic variants associated withthe interindividuality of response to dietary treatments for weight loss. These nutritional genomics efforts contribute to theadvancement of nutrition science 4.0: preventive, participatory, predictive and personalized. However, although to date morethan 85 million polymorphisms have been discovered in the human genome, these findings do not indicate that the presenceof these variations determines an effect on a personal health. Therefore, the use of the nutrigenetic profile for weight loss leadsto analyze the risks/benefits with the bioethical principles focused on the unity, individuality and uniqueness of the humanperson. Thus, based on classical thinkers such as Aristotle and Thomas Aquinas, but with the contribution of contemporaryphilosophers, such as Robert Spaemman, the person is defined as an individual substance of a rational nature, breaking downthe fundamental dimensions to demonstrate, by argumentation, that the principle individuality not only includes the biologicaldimension (materialistic naturalism), but the unity of the person belonging to human nature.